10 A/567 V normally off p‐GaN gate HEMT with high‐threshold voltage and low‐gate leakage current. Issue 13 (1st June 2018) - Hao, Ronghui; Wu, Dongdong; Fu, Kai; Song, Liang; Chen, Fu; Zhao, Jie; Du, Zhongkai; Zhang, Bingliang; Wang, Qilong; Yu, Guohao; Cheng, Kai; Cai, Yong; et al.
Abstract : Normally off p‐gallium nitride (GaN) gate high‐electron‐mobility transistors (HEMTs) on silicon substrate were fabricated with hydrogen plasma treatment technology, which features a high‐resistivity cap layer (HRCL) at the access region. With hydrogen plasma treatment at the access region, the normally off operation was obtained with a threshold voltage of +2.5 V based on the linear extrapolation of the transfer curve. The fabricated HRCL‐HEMT with a gate width of 49.7 mm exhibits a maximum drain current of 10 A at V GS = 8 V and a high off‐state breakdown voltage of 567 V at V GS = 0 V with substrate grounded. Meanwhile, the HRCL‐HEMT also shows low‐gate leakage current of 1.3 × 10 −7 and 3.3 × 10 −10 A/mm at V GS = 8 V and = −30 V, respectively. The positive threshold voltage, high drain current, high‐breakdown voltage and low‐gate leakage show the potential of HRCL‐HEMT for power switching applications.